A New Frontier in Science Communication? What We Know About How Public Audiences Respond to Cinematic Scientific Visualization - Jensen, Eric A.; Borkiewicz, Kalina Maria; Naiman, Jill P. (Frontiers in Communication, 2022)
Presenting data in visually appealing formats has long been a useful science communication technique. Millions of people around the world have encountered scientific visualizations through documentary films on giant and small screens. Borkiewicz et al. (2019, p. 11) have argued that science should “make use of visual effects tools [to] allow for the creation of higher-fidelity visualizations that meet the high bar set by modern cinema”. Specifically, cinematic scientific visualization should be (a) based on real data, (b) understandable and (c) entertaining for a general public audience. To investigate what is known about how audiences respond to this type of science communication, this essay presents an overview of the literature on this topic, highlighting key findings, gaps and directions for future research. The sprawling nature of the theoretical and empirical research literature on audience responses to cinematic scientific visualization makes it difficult to achieve comprehensive coverage of relevant studies and theoretical models. Recurring methodological limitations present further challenges to establishing a foundation of reliable knowledge on this topic. Nevertheless, prior research has identified several factors that affect how public audiences respond to cinematic scientific visualizations. Here, we discuss findings relating to intelligibility, film content and immersion. These results offer a basis for hypotheses to be tested by future confirmatory studies of audience responses to cinematic scientific visualizations.